2022
DOI: 10.1002/advs.202105668
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Quantum Dot‐Armed Bacteriophage for Combating Drug‐Resistant Bacterial Infection

Abstract: Multidrug‐resistant (MDR) bacterial infection is one of the greatest challenges to public health, a crisis demanding the next generation of highly effective antibacterial agents to specifically target MDR bacteria. Herein, a novel photocatalytic quantum dot (QD)‐armed bacteriophage (QD@Phage) is reported for combating green fluorescent protein‐expressing Pseudomonas aeruginosa (GFP‐P. aeruginosa) infection. The proposed QD@Phage nanosystem not only specifically binds to the host GFP‐P. aeruginosa while preserv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In addition, some new materials such as nanoparticles, a class of emerging antibacterial agents, exhibit an antibacterial mechanism that includes the destruction of bacterial biofilms, and many innovative anti-biofilm nanomedicines and nanomaterials have been developed for clinical treatment (Xiu et al, 2021). A recent study developed a novel photocatalytic quantum dot-armed bacteriophage nanosystem that combined phage therapy and photodynamic therapy, not only specifically binding to host P. aeruginosa, but also targeting host bacteria through the inherent infectivity of phages, locally generating massive amounts of ROS under visible light irradiation, and thereby demonstrating potent anti-biofilm activity (Wang et al, 2022). However, microorganisms adhere to the surfaces of medical devices and are prone to forming biofilms, leading to inevitable and challenging issues with P. aeruginosa biofilm infection caused by the use of clinical medical devices (Wi and Patel, 2018).…”
Section: Conclusion and Prospective Applicationsmentioning
confidence: 99%
“…In addition, some new materials such as nanoparticles, a class of emerging antibacterial agents, exhibit an antibacterial mechanism that includes the destruction of bacterial biofilms, and many innovative anti-biofilm nanomedicines and nanomaterials have been developed for clinical treatment (Xiu et al, 2021). A recent study developed a novel photocatalytic quantum dot-armed bacteriophage nanosystem that combined phage therapy and photodynamic therapy, not only specifically binding to host P. aeruginosa, but also targeting host bacteria through the inherent infectivity of phages, locally generating massive amounts of ROS under visible light irradiation, and thereby demonstrating potent anti-biofilm activity (Wang et al, 2022). However, microorganisms adhere to the surfaces of medical devices and are prone to forming biofilms, leading to inevitable and challenging issues with P. aeruginosa biofilm infection caused by the use of clinical medical devices (Wi and Patel, 2018).…”
Section: Conclusion and Prospective Applicationsmentioning
confidence: 99%
“…The proposed QD@Phage nanosystem not only specifically bound to the host GFP-P. aeruginosa while preserving the infectivity of the phage itself, but also showed a superior capacity for synergistic bacterial killing by phage and by the photocatalytic localized ROS generated from anchored QD component (Figure 36D). 297 In addition to the above modification methods, some emerging novel modification strategies have been developed for the construction of advanced and efficient photocatalytic antibacterial materials. For example, recent studies have shown that loading metal single atoms onto photocatalysts can greatly enhance the photoresponse performance of photocatalysts, the separation of e − /h + pairs, the catalytic surface reactions kinetics, and ultimately improve the ROS production efficiency and photocatalytic antibacterial performance.…”
Section: Constructing Heterostructures By Semiconductor Combinationmentioning
confidence: 99%
“…(D) A novel photocatalytic QD-armed bacteriophage: (I) a schematic illustration is provided to depict the phage-assisted photocatalytic therapy targeting GFP- P. aeruginosa ; (II) The bacterial viability of GFP- P. aeruginosa and MRSA after the light treatment with QD labeled phages. Reproduced with permission from ref . Copyright 2022, Wiley and Sons under [CC BY-NC-ND 4.0] [].…”
Section: Design Strategies For Improving Photocatalytic Performancementioning
confidence: 99%
“…[9] To overcome these limitations, Peng et al [10] prepared chimeric M13 phages to broaden the antibacterial spectrum and combined with gold nanorods to ablate various bacterial species by photothermal ablation. Wang et al [11] reported a photocatalytic quantum-dot-armed phage (QD@phage) for combating Pseudomonas aeruginosa infection. QD@phage preserved specifically binding ability of phages to assist QD localization on the surfaces of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. [ 11 ] reported a photocatalytic quantum‐dot‐armed phage (QD@phage) for combating Pseudomonas aeruginosa infection. QD@phage preserved specifically binding ability of phages to assist QD localization on the surfaces of bacteria.…”
Section: Introductionmentioning
confidence: 99%